2021
DOI: 10.5897/jco2020.0221
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability analysis in sunflower (Helianthus annuus L.) genotypes

Abstract: Eight sunflower inbred lines were crossed in 8×8 diallel fashion (without reciprocal) and 28 F 1 were developed at Oilseed Research Centre (ORC), Bangladesh Agricultural Research Institute (BARI), Gazipur in Rabi season, 2018. All F 1 and their parents were planted in Rabi season 2019 to estimate general combining ability (GCA) and specific combining ability (SCA) effects for yield and yield attributes. The highly significant mean squares for genotypes for all the studied characters indicating wide variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…To increase the yield in sunflower vertically, development of hybrids with better yield potential and stability is required. Parents with diverse genetic makeup would generally produce superior transgressive hybrids 48 . To make a breeding program fruitful, the first step is to select the parental lines to be used for hybridization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase the yield in sunflower vertically, development of hybrids with better yield potential and stability is required. Parents with diverse genetic makeup would generally produce superior transgressive hybrids 48 . To make a breeding program fruitful, the first step is to select the parental lines to be used for hybridization.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of both significant GCA and SCA effects in the present study indicates the presence of both additive and non-additive gene effects in the expression of plant measured traits. GCA effects generally lead to the selection of suitable parents for population improvement or development of synthetics or composite cultivars, as these may be the preference of some growers because their seed can be used for more than one year 48 . In present study, high and significant GCA effects for both among CMS and restore lines in desirable directions i.e., negative for flowering, maturity, and plant height traits and positive for the rest of traits measured was observed.…”
Section: Discussionmentioning
confidence: 99%
“…11 & 12). Habib et al (2021) and Khan et al (2008) had reported variability for no of achenes per head in sunflower.…”
Section: No Of Achenes Per Headmentioning
confidence: 96%
“…Crosses showing largest head diameter might be utilized in producing a greater number of achenes per head and ultimately high yielding hybrids. Habib et al (2021) and Khan et al (2008) had reported variability for head diameter in sunflower ranged from 8.51 to 24.46 cm. The above listed findings are in comparisons with these researchers.…”
Section: Fresh Head Diameter (Cm)mentioning
confidence: 97%
“…After canola, palm, and soybean, it is the fourth most significant oilseed crop (Farrokhi et al, 2011). In 2019-20, despite a minor decline in cottonseed and sunflower seed production, global oilseed production was virtually unchanged at 610.42 million tonnes (Sheikh et al, 2021). It includes between 40 and 50 percent oil and 23 percent protein, which is a substantial amount.…”
Section: Introductionmentioning
confidence: 99%